Trichinella spiralis paramyosin activates mouse bone marrow-derived dendritic cells and induces regulatory T cells - Guo, Kai (Parasit Vectors, 2016)
BACKGROUND: Dendritic cells (DCs) are antigen-presenting cells that regulate T cell responses for many infectious diseases. The tissue-dwelling nematode Trichinella spiralis expresses paramyosin (TsPmy) not only as a structural protein but also as an immunomodulator to alleviate complement attack by binding to some host complement components. Whether TsPmy is involved in other immunomodulatory pathway and how TsPmy interacts with host DCs is still unknown. METHODS: Mouse bone marrow-derived DCs were incubated with recombinant TsPmy (rTsPmy) for activation. Maturation of DC was determined by the expression of surface markers CD40, CD80, CD86 and MHCII. The rTsPmy-pulsed DCs were co-incubated with T. spiralis-sensitized or naïve mouse CD4(+) T cells to observe their activation on T cells and polarizing regulatory T cells using flow cytometry. Cytokines were measured by enzyme-linked immunosorbent assays (ELISA). RESULTS: TsPmy was able to activate mouse bone marrow-derived DCs to semi-mature status characterized by expressing surface CD40 and CD86, but not CD80 and MHCII. The semi-mature TsPmy-pulsed DCs were able to stimulate T. spiralis-sensitized CD4(+) T cells to proliferate. Incubation of TsPmy-pulsed DCs with naïve CD4(+) splenocytes polarized the latter to CD4(+)CD25(+)Foxp3(+) regulatory T cells. However, mice immunized with rTsPmy only induce the CD4(+)CD25(−)Foxp3(+) T cell population, associated with high level of IL-10, TGF-β and IL-17A. CONCLUSIONS: During T. spiralis infection, TsPmy plays an important role in modulating the host immune system by stimulating DCs to differentiate the CD4(+) T cells to regulatory T cells, in addition to binding to components of the host complement cascade, as survival strategies to live in host.